STRATEGI IMPLEMENTASI TIK DAN KOMPETENSI PEDAGOGIK GURU TERHADAP PERUBAHAN PEMBELAJARAN SEKOLAH MENENGAH PERTAMA DI KOTA SEMARANG - Wanty Eka Jayanti (Universitas Bina Sarana Informatika, 2013)
This study aimed to identify the influence of implementation of ICT strategies of pedagogical competence of teachers and changes in student learning at the junior high schools in Semarang City. The number of respondents in this study as many as 188 people, with the status as a teacher Junior High School (SMP) in Semarang with a minimum of 3 years working lives and administer subjects using multimedia instructional media were selected by purposive sampling method.Mechanical testing of the data used in this peneiltian include test validity with factor analysis, reliability testing with Cronbach alpha formula, multiple regression analysis, keofisien determination, F test, t test to validate research hypothesis and test to analyze the effects of mediating variables mediating effect of motivation.The research proves that (1). ICT implementation strategies have a significant effect on teachers pedagogical competence, (2). ICT implementation strategies have a significant effect on changes in student learning, and (3). Pedagogical competence of teachers have a significant effect on changes in student learning.Key words: Learning, Pedagogical, ICT.